Heat stress is overestimated in climate impact studies for irrigated agriculture - Stefan Siebert; Heidi Webber; Gang Zhao; Frank Ewert (Environmental Research Letters, 2017)
Climate change will increase the number and severity of heat waves, and is expected to negatively affect crop yields. Here we show for wheat and maize across Europe that heat stress is considerably reduced by irrigation due to surface cooling for both current and projected future climate. We demonstrate that crop heat stress impact assessments should be based on canopy temperature because simulations with air temperatures measured at standard weather stations cannot reproduce differences in crop heat stress between irrigated and rainfed conditions. Crop heat stress was overestimated on irrigated land when air temperature was used with errors becoming larger with projected climate change. Corresponding errors in mean crop yield calculated across Europe for baseline climate 1984–2013 of 0.2 Mg yr ^−1 (2%) and 0.6 Mg yr ^−1 (5%) for irrigated winter wheat and irrigated grain maize, respectively, would increase to up to 1.5 Mg yr ^−1 (16%) for irrigated winter wheat and 4.1 Mg yr ^−1 (39%) for irrigated grain maize, depending on the climate change projection/GCM combination considered. We conclude that climate change impact assessments for crop heat stress need to account explicitly for the impact of irrigation.